The Structural Origins of Racial Inequality and Attitudes Toward Redistribution - Christiani, Leah (Race and social problems, 2025)
A long line of research demonstrates that priming race undermines support for redistribution by activating negative racial stereotypes that tend to place blame for racial inequalities on individual members of minoritized groups and downplay the systemic causes of racial inequality. Here we suggest that information emphasizing the structural origins of racial disparities can disrupt these typical patterns and generate more positive attitudes toward redistributive policies because structural narratives run counter to individualistic racial stereotypes. To evaluate this possibility, we conduct a novel survey experiment that assesses how exposure to information about the structural underpinnings of racial inequality affects redistribution attitudes. Our analysis shows that support for redistributive policies increases after exposure to our treatment, with the effect most pronounced among White Republicans and those with high levels of racial resentment. These findings suggest that how we talk about racial inequality matters—focusing on structural accounts can bolster support for redistribution, especially among those groups least likely to support egalitarian policies overall.